Evaluation, development and implementation of a shunt power quality compensator under unbalanced conditions - Pittorino, L. A.(Leonardo Andres) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.